Hubungan Keperawatan Syariah dengan Loyalitas Pasien - Saikha Nabila Hasna; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Sharia nursing is often applied in health services with Islamic standards which aim to maintain boundaries between members of the opposite sex and respect religious values. This practice is expected to increase patient satisfaction and loyalty, especially those who are predominantly Muslim. To prevent errors, hospitals and medical personnel need to prepare service standards and have a good understanding of sharia nursing. This study aims to analyze whether there is a correlation between sharia nursing and patient loyalty. This is a quantitative research with a cross-sectional approach. Data collection using a questionnaire. Population in this study amounted to 749 people. This study used 260 respondents using non-probability sampling techniques with purposive sampling methods. Data obtained were processed using the Spearman rank test. Results of this study indicate that the majority of respondents to sharia nursing are in the high category with a total of 230 (88.5%) respondents, while patient loyalty with the most respondents is in the high category with a total of 242 (93.1%) respondents. results of the statistical test obtained a p-value: 0.000 with a closeness of 0.456 which means that there is a correlation between sharia nursing and patient loyalty with a strong level of closeness. There is a significant correlation between sharia nursing and patient loyalty with (p-value <0.05).